Estimación de la biomasa aérea y carbono almacenado de los árboles de la zona urbana del Parque Nacional Enrique Olaya Herrera a partir del Índice de Vegetación de Diferencia Normalizada (NDVI) (2023)
The estimation of the aboveground biomass and stored carbon in the urban area of Enrique Olaya Herrera National Park located in Bogotá, Colombia was carried out. To achieve this, a model generated by polynomial regression was used, using the Normalized Difference Vegetation Index (NDVI) as the predictor variable, which yielded an R2of 0.0128.